SELECTION OF THE WARSHIP AS AN AUXILIARY SHIP FOR THE DISTRIBUTION OF AMMUNITION TO SUPPORT THE NAVY TASK - Adi Wirasmo; Mukhlis Mukhlis; Rakhmad Susilo (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2022)
Arsenal is a work unit that has the responsibility of storing, maintaining, and distributing weapons and ammunition supplies has not been able to support optimally because there is only one Arsenal, and must serve user units like the Indonesian Naval Base. spread throughout Indonesia and there is no special transportation of ammunition to distribute so the process of distributing ammunition depends on the element of the title. Distribution constraints faced with existing conditions will be planned for the selection of KRI in the assignment as an auxiliary ammunition ship. This study aims to determine the selection of the best ship for the assignment as an ammunition auxiliary ship using the Analytic Network Process (ANP) method. The use of the ANP method is based on the existence of data that has a relationship between criteria and a relationship between subcriteria. There are two main criteria used in conducting alternative selection, namely operational requirements criteria with five sub-criteria: Security, Geographical conditions, mobility, ship worthiness, sailing resistance, and technical requirements criteria with five sub-criteria: machining, navigation, platform safety equipment as well as sensors. The results of this study are an alternative priority for the selection of ships in the assignment as ammunition auxiliary ships to carry out the distribution of ammunition throughout the Indonesian Naval Base. The best alternative based on the main criteria and sub-criteria is the type of personnel transport auxiliary ship (BAP) with a score of 0.341260. Keywords: Assignment, Analytic Network Process (ANP), and Auxiliary Ship for Ammunition.